Learning Nessus for penetration testing : master how to perform IT infrastructure security vulnerability assessments using Nessus with tips and insights from real-world challenges faced during vulnerability assessment /: master how to perform IT infrastructure security vulnerability assessments using Nessus with tips and insights from real-world challenges faced during vulnerability assessment. (2014) - Unknown
No abstract available